2009
DOI: 10.2139/ssrn.1618125
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Household Behavior in the Philippines

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 19 publications
(22 reference statements)
4
35
0
Order By: Relevance
“…Vasco (2013), studying migration and remittances in the case of rural Ecuador finds that "neither migration nor remittances have any effect on the odds of a household owning a rural business" (Vasco 2013: 37). Ang et al (2009) also do not find a significant effect of remittances on productive investments in the Philippines.…”
Section: Are Migrant Remittances Likely To Fund Entrepreneurship In Tmentioning
confidence: 58%
“…Vasco (2013), studying migration and remittances in the case of rural Ecuador finds that "neither migration nor remittances have any effect on the odds of a household owning a rural business" (Vasco 2013: 37). Ang et al (2009) also do not find a significant effect of remittances on productive investments in the Philippines.…”
Section: Are Migrant Remittances Likely To Fund Entrepreneurship In Tmentioning
confidence: 58%
“…However, this inconclusive result attributed to measurement difficulties arising from the fact that remittances may behave countercyclical with respect to growth. Faini [44] and Ang [13] found that the impact of remittances on growth is positive. Faini [44] argues that remittances overcome capital market imperfections and allow migrant households to accumulate positive assets.…”
Section: Introductionmentioning
confidence: 99%
“…Faini [44] argues that remittances overcome capital market imperfections and allow migrant households to accumulate positive assets. Ang [13] shows the relationship between workers' remittances and economic growth at the national and at the regional levels in the case of Philippines. He found that at the national level remittances do influence economic growth positively and significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The co‐operative was organised to help land reform beneficiaries – formerly landless plantation workers – obtain farmland. Although land reform beneficiaries are expected to be eager to take up farming as new landowners, the Philippines is also known for its highly diversified rural communities with a high incidence of emigration (Ang et al ., ). In this setting, a variety of diversification can be observed explicitly.…”
Section: Introductionmentioning
confidence: 99%